Gang Affiliation in Adolescence and Attachment in Infancy - Unis, Joan E. (2001)
According to Attachment Theory (Bowlby, 1969, 1973, 1980), infants become attached to their primary caregiver for protection and security. Gang literature reports that individuals join gangs for the companionship and protection a gang can offer (Hochhaus & Sousa, 1987-88; Friedman, Mann, & Friedman, 1975). The aim of this present study was to examine the proposition that individuals who eventually become gang members in adolescence have an insecure attachment to caregivers, a secure attachment to peers, and will have lower scores on constructs related to attachment. The participants in this study were 90 individuals, divided equally into gang and non-gang members. All participants were given four separate attachment measures to assess attachment classification (The Security Scale, The Inventory of Parent and Peer Attachment, The Behavioral Systems Questionnaire, and the Attachment Style Scale) for both parents and peers, as well as three measures of attachment correlates. There was minimal support for the proposed hypotheses relating to insecure attachment. The results are discussed from the perspective of attachment theory